Liraglutide Lowers Palmitoleate Levels in Type 2 Diabetes. A Post Hoc Analysis of the LIRAFLAME Randomized Placebo-Controlled Trial - Wretlind, Asger; Zobel, Emilie Hein; de Zawadzki, Andressa; Ripa, Rasmus Sejersten; Curovic, Viktor Rotbain; von Scholten, Bernt Johan; Mattila, Ismo Matias; Hansen, Tine Willum; Kjær, Andreas; Vestergaard, Henrik; Rossing, Peter; Legido-Quigley, Cristina (Frontiers in Clinical Diabetes and Healthcare, 2022)
Background Liraglutide is a glucose-lowering medication used to treat type 2 diabetes and obesity. It is a GLP-1 receptor agonist with downstream metabolic changes beyond the incretin system, such as reducing the risk of cardiovascular complications. The understanding of these changes is critical for improving treatment outcomes. Herein, we present a post hoc experimental analysis using metabolomic phenotyping to discover molecular mecphanisms in response to liraglutide. Method Plasma samples were obtained from The LiraFlame Study (ClinicalTrials.gov identifier: <uri xlink:href="http://rghsap002.regionh.top.local:50100/irj/servlet/prt/portal/prtroot/pcd!3aportal_content!2fevery_user!2fgeneral!2fdefaultAjaxframeworkContent!2fcom.sap.portal.standalonecontentarea?NavigationTarget=navurl%3A%2F%2F0e7a2b5827ab09848a43c33c1d8b38c9&ExecuteLocally=true&DrillDownLevel=1&CurrentWindowId=WID1641804574972&supportInitialNavNodesFilter=true&PrevNavTarget=navurl%3A%2F%2F2e6584247abf8533ed33a582eda54cd5&NavMode=1" xmlns:xlink="http://www.w3.org/1999/xlink">NCT03449654), a randomized double-blinded placebo-controlled clinical trial, including 102 participants with type 2 diabetes randomized to either liraglutide or placebo treatment for 26 weeks. Mass spectrometry-based metabolomics analyses were carried out on samples from baseline and the end of the trial. Metabolites (n=114) were categorized into pathways and linear mixed models were constructed to evaluate the association between changes in metabolites and liraglutide treatment. Results We found the free fatty acid palmitoleate was significantly reduced in the liraglutide group compared to placebo (adjusted for multiple testing p-value = 0.04). The activity of stearoyl-CoA desaturase-1 (SCD1), the rate limiting enzyme for converting palmitate into palmitoleate, was found significantly downregulated by liraglutide treatment compared to placebo (p-value = 0.01). These metabolic changes have demonstrated to be linked to insulin sensitivity and cardiovascular health.